Purified Cytoplasmic Pollen (PCP) Extract: A Novel Approach to The Treatment of Menopausal Symptoms - Lyon Clement (Cermin Dunia Kedokteran, 2024)
During the menopause transition, several symptoms such as muscle and joint pain, back pain, vasomotor symptoms, urogenital symptoms, and psychological disorders may occur due to declining estrogen levels. Approximately a third of women would experience severe symptoms with a need for treatment. Currently, menopausal hormonal therapy (MHT) is still considered to be the first-line therapy despite its risk of cancer. Other options, such as pharmacotherapy or herbal formulas, have their limitation, urging the need for an effective and safe treatment. Standardized purified cytoplasmic pollen (PCP) extract, otherwise known as PureCyTonin® is a novel, non-hormonal, non-phytoestrogenic option that is proven to be effective in reducing menopausal symptoms while being neutral to the proliferation and apoptosis of breast cancer cells. Recent evidence shows promising results of PureCyTonin® for menopausal symptoms treatment.